MANAJEMEN SARANA DAN PRASARANA DALAM MENINGKATKAN EFEKTIVITAS LAYANAN ADMINISTRASI SEKOLAH Di MA BAHRUL ULUM BESUK - Moh Abdul Wasik (Jurnal Mahasiswa: Jurnal Ilmiah Penalaran dan Penelitian Mahasiswa, 2022)
The purpose of this research is to find out how the process of planning, organizing, implementing and monitoring facilities and infrastructure at Madrasah Aliyah Bahrul Ulum Besuk, which are still not in accordance with standard facilities and infrastructure. The researcher found that administrative services at Madrasah Aliyah Bahrul Ulum Besuk were already running, but were not as appropriate as they should be. This can be seen from the inadequate facilities and infrastructure, such as the lack of facilities and infrastructure for learning practices at Madrasah Aliyah Bahrul Ulum Besuk. For example classrooms, practice rooms, administration rooms and other facilities. This type of research is qualitative research, namely data collected in the form of words, pictures, not numbers. Based on the description of the data and discussion of the research results, it can generally be concluded that the management of management facilities and administrative infrastructure at Madrasah Aliyah Bahrul Ulum Besuk is going well although there are still weaknesses in the availability of administrative room facilities which are still in bulkheads, reduction of chemical laboratories, glass, biology, language and computers.